Pharmacist interventions throughout care transitions: a review of current practices - Testman, Julie A.; Teichman, Anne E.; Cook, Stephen J.; Kimble, Angel; Riley, Brittany L.; Robinson, Jessica; Snodgrass, Brittany (International Current Pharmaceutical Journal, 2013)
Transitions of care occur each time a patient moves from one healthcare provider or care setting to another. Challenges that have been identified include: failure of the patient to keep appointments for outpatient chronic care; inability for smooth transfer of information between various healthcare providers; and failure to find appropriate placement for patients who can no longer manage independent living. As pharmacists representing an array of practice settings, these authors here present the models of contributions made by pharmacy services within such multifaceted approaches. An initial literature search was conducted using the National Library of Medicine via PubMed. Studies conducted in the United States that included at least one pharmacy service within the methods of intervention were selected for review. Where there are published findings from each setting, we include the measured impact, if reported. Although pharmacists represent the most skilled healthcare professionals in medication reconciliation and management, the best processes for tapping that expertise have yet to be fully elucidated. We present this review of current practices with the continued hope that the pharmacy profession will, not only continue to be the quiet patient advocate for best medication use, but also to open our minds to the need to measure, adjust, and measure again, the systems and processes we use to best integrate our knowledge for the overall benefit of the patient. DOI: http://dx.doi.org/10.3329/icpj.v2i10.16409 International Current Pharmaceutical Journal, September 2013, 2(10): 159-164